Monitoring the Future: A Continuing Study of American Youth (8th- and 10th-Grade Surveys), 2020 - Miech, Richard A. ([Verlag nicht ermittelbar], 2021)
These surveys of 8th- and 10th-grade students are part of a series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth. Students in each grade are randomly assigned to complete one of four questionnaires, each with a different subset of topical questions but containing a set of "core" questions on demographics and drug use. There are more than 500 variables across the questionnaires. Drugs covered by this survey include amphetamines (stimulants), barbiturates (tranquilizers), other prescription drugs, over-the-counter medications, tobacco, smokeless tobacco, vaping, alcohol, inhalants, steroids, marijuana, hashish, LSD, hallucinogens, cocaine, crack, ecstasy, methamphetamine, and injectable drugs such as heroin. Highlights for 2020: All students recorded their survey answers on tablets that the project brought to the schools, preloaded with the MTF surveys. Data collection was halted prematurely on March 15, 2020 when the University of Michigan stopped all projects that involved face-to-face data collection because of COVID-19 concerns. This resulted in a 2020 sample size about 25% the size of a regular data collection. Guidance for combining grades for analysis: see Appendix C of the codebook Information about potential mode effects for questions on student attitudes and beliefs when comparing previous years' paper-based survey responses to the current tablet method of collection. Please see the codebook Introduction - Survey Mode section for details.